1973
DOI: 10.1038/bjc.1973.183
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dimethylhydrazine Induced Tumours in Mice as a Model System for Colorectal Cancer

Abstract: Summary.-The evolution and structure of adenomatous polyps and adenocarcinomata of the colon in NMRI mice induced by dimethylhydrazine are described. Severe toxic reactions in the liver and other organs are produced by dimethylhydrazine (DMH), but tumours are induced only in the colon and around the anus.The 100%o incidence and growth characteristics of the tumours make it potentially a good model system, but investigators should take into account the widespread nonspecific cellular injury induced by this carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
1

Year Published

1974
1974
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 9 publications
1
14
0
1
Order By: Relevance
“…An increase in the activity of these enzymes could possibly enhance the catabolism of carbohydrate containing macromolecules. It may also explain the lack of PAS or alcian blue staining in the sections of colonic tumours (Rogers et al, 1973;Haase et al, 1973).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increase in the activity of these enzymes could possibly enhance the catabolism of carbohydrate containing macromolecules. It may also explain the lack of PAS or alcian blue staining in the sections of colonic tumours (Rogers et al, 1973;Haase et al, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…The rats and mice were given a weekly dose of 20 mg and 20 mg per kg body weight, respectively. The DMH solution was freshly made up in sodium EDTA solution each time as described previously (Haase et al, 1973). The control animals were injected with sodium EDTA in saline alone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors observed that in the experimental mice the last 4 cm of the colon was always the site of at least one polyp. A gradient in the cell turnover times from the proximal to the distal end of the colon and a considerable variation in the cell proliferation rates in the DMH induced mouse colonic tumours and in the primary adenocarcinomata of the human large bowel have already been observed (Sawicki and Rowinski, 1970;Haase et al, 1973;Bottomley and Cooper, 1973;Camplejohn, Bone and Aherne, 1973).The present work was carried out to assess the enzymatic heterogeneity among the DMH induced rat colonic tumours with reference to the site specificity and variations in tumour morphology and cell kinetics. …”
mentioning
confidence: 96%
“…Evidence of a generalized change, as indicated by an overall reduction of 35S uptake, in parts of the DMH treated rat colon where tumours were commonly developed has been given (Springer, Springer and Oehlert, 1970). The site where tumours would arise in the mouse colon after DMH treatment could be predicted with great certainty (Haase et al, 1973). These authors observed that in the experimental mice the last 4 cm of the colon was always the site of at least one polyp.…”
mentioning
confidence: 99%